The Nature of Interest and the Causes of Its Fluctuations - McGoun, A. F. (Quarterly Journal of Economics, 1917)
I. Capital defined as wealth produced by labor and destined to satisfy wants in the future, 547. — The possibility of interest due to the fact that capital saves labor, 550. — Concrete illustration of the saving, 551. — II. Illustration of the circumstances which may affect the rate of interest under hypothetical conditions, the main conclusions of the present essay being suggested. — Capital quantitatively expressed in terms of labor multiplied by the time intervening between labor and enjoyment, 553. — III. Circumstances affecting the demand for capital: (a) The opening of new lands, 557. — (b) Inventions, 560. — Under certain conditions the ultimate effect of these circumstances is opposite to their immediate effect, 561. — (c) Variations in the aggregate consumption of society, 563. — Effect of such variations on the supply of capital, 564. — Supply of capital also affected by the quantity of labor expended, 567; which for a given population depends on the amount of leisure enjoyed and on the efficiency of labor, 568. — Conclusion on ultimate causes permanently affecting the rate of interest. — Why capital has always been able to earn interest, 569.